PERTUKARAN SOSIAL DALAM HOOK UP CULTURE DI APLIKASI KENCAN DARING BUMBLE - Galuh Gayatri, I Gusti Agung Ayu; Krisna Aditya, I Gusti Ngurah Agung; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This study aims to examine the processes of social interaction that occur between the users of Bumble, an online dating application. Within this context, the dynamic and complex mechanisms of social interaction create an intriguing situation worthy of further analysis. This study aims to comprehend how Bumble users form relationships built upon a concept of cost vs. reward, as well as the process in which these users form mutually beneficial agreements through the affairs of social interaction. By using a qualitative descriptive-explanative method, the researcher explores this concept further by assessing the personal experiences of eight different individuals, selected using a set of specific criteria. The data used in this study is collected via semi-structured interviews, and later analyzed to identify the ongoing mechanisms of social interaction. This analysis accounts for additional factors, such as the subjective preferences affecting the social dynamics within hook up culture. The findings of this study have revealed that social exchanges between Bumble users does not just have a material aspect, but also an emotional and psychological one. The various costs in these social interactions include emotional risk, time, and energy, while the rewards include emotional and sexual fulfillment, as well as social validation. This study also finds that social interaction can take a noticeable variety of forms depending on each individual’s wants and needs. In some cases, the ongoing social interaction reflects a mutually beneficial situation, while in others, these interactions are cut short by an imbalance between the relationship’s cost and reward. This study is intended to give deeper insight on how online dating applications, such as Bumble, cause the developments of new social interaction patterns in the digital era, and more specifically within the context of hook up culture. This study will ideally become a valuable contribution to the field of sociology, communication, and other related fields of study.